Navigator Notes: Editorial Highlights from the Editor-in-Chief - Richard B. Langley (Navigation)
Welcome to the Winter 2024 issue of NAVIGATION. In this issue, we again feature articles on a wide range of topics on positioning, navigation, and timing including navigation underground, in urban canyons, for Earth-orbiting satellites, and even on the Moon. All that and very much more.